2000
DOI: 10.1046/j.1365-313x.2000.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

A high throughput system for transposon tagging and promoter trapping in tomato

Abstract: SummaryWe describe new tools for functional analysis of the tomato genome based on insertional mutagenesis with the maize Ac/Ds transposable elements in the background of the miniature cultivar Micro-Tom. 2932 F 3 families, in which Ds elements transposed and were stabilized, were screened for phenotypic mutations. Out of 10 families that had a clear mutant phenotype, only one mutant was Ds-tagged. In addition, we developed promoter trapping using the ®re¯y luciferase reporter gene and enhancer trapping, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 43 publications
1
82
0
6
Order By: Relevance
“…Additionally, it was shown that a collection of tomato mutants in a single tomato background represented by MT could be of great value to study AM development under different edaphic conditions. The availability of large populations of MT insertional mutants (Meissner et al, 2000;Mathews et al, 2003) and ESTs databases specific for this cultivar (Yano et al, 2005) provide convenient tools for further studies on the molecular mechanisms controlling AM development.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was shown that a collection of tomato mutants in a single tomato background represented by MT could be of great value to study AM development under different edaphic conditions. The availability of large populations of MT insertional mutants (Meissner et al, 2000;Mathews et al, 2003) and ESTs databases specific for this cultivar (Yano et al, 2005) provide convenient tools for further studies on the molecular mechanisms controlling AM development.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency of Ds to transpose to linked sites has also been exploited to disrupt genes present in tandem arrays (Takken et al 1999;Tantikanjana et al 2004) and to perform localized saturation mutagenesis (Nishal et al 2005). Ac/Ds mutagenesis platforms in Arabidopsis (Sundaresan et al 1995;Ito et al 1999;Muskett et al 2003;Kuromori et al 2004), tomato (Healy et al 1993;Knapp et al 1994;Meissner et al 2000), tobacco (Scofield et al 1992), rice (Chin et al 1999;Zheng-Ge et al 2003;Kim et al 2004;Kolesnik et al 2004), and barley (Koprek et al 2000;Cooper et al 2004) have been developed. Yet, despite the demonstrated utility of Ds in gene tagging in maize (Hake et al 1989;Colasanti et al 1998), a two-component Ac/Ds genetagging program for this important crop plant has not yet been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the transposon flanking regions was performed by long-range inverse PCR as described previously (Meissner et al, 2000). The wildtype ORR locus and the insertion allele were genotyped by oligonucleotides 1 and 2 (1149-bp amplicon) and 1 and 3 (808 bp), respectively (see Supplemental Table 4 online).…”
Section: Isolation Of the Orr Ds Insertion And Genotypingmentioning
confidence: 99%